Towards the Development of a Female Animal Model of T1DM Using Hyaluronic Acid Nanocoated Cell Transplantation: Refinements and Considerations for Future Protocols - Fernanda Zamboni; Ibrahim F. Cengiz; Ana M. Barbosa; Antonio G. Castro; Rui L. Reis; Joaquim M. Oliveira; Maurice N. Collins (MDPI AG, 2021)
Female mice (Black 6 strain) (C57BL/6) aged 6 weeks were subject to low dose streptozotocin (STZ) treatment for five consecutive days to mimic type 1 diabetes mellitus (T1DM) with insulitis. At two weeks after STZ injections, evaluation of the elevated glucose levels was used to confirm diabetes. The diabetic mice were then subject to the transplantation of pancreatic β-cells (MIN-6 line). Four groups of mice were studied. The first group was injected with saline-only acting as the placebo surgery control, also known as SHAM group, the second and third groups were injected with MIN-6 single cells and polyethylene glycol-modified dipalmitoyl-glycerol-phosphatidyl ethanolamine (PEG-DPPE) modified MIN-6 single cells (500 µg per 1.106 cells), respectively, while the fourth group was injected with hyaluronic acid (HA)-coated MIN-6 single cells (5 bilayers). At seven- and fourteen-days following transplantation, the mice were euthanised. The renal and pancreatic tissues were then collected and histologically analysed. The induction of diabetes in female mice, through five-consecutive daily STZ injections resulted in inconsistent glycaemic levels. Interestingly, this shows an incomplete diabetes induction in female mice, of which we attribute to sex dimorphism and hormonal interferences. Transplantation failure of free-floating encapsulated cells was unable to decrease blood glucose hyperglycaemia to physiological ranges. The result is attributed to deprived cell-cell interactions, leading to decreased β-cells functionality. Overall, we highlight the necessity of refining T1DM disease models in female subjects when using multiple low-dose STZ injections together with transplantation protocols. Considerations need to be made regarding the different developmental stages of female mice and oestrogen load interfering with pancreatic β-cells susceptibility to STZ. The use of pseudo islets, cell aggregates and spheroids are sought to improve transplantation outcome in comparison to free-floating single cells.